Authorities and Responsibilities of Notaries Regarding the Implementation of Cyber Notary in Indonesia - Iqbal Pandu Satrio (Authentica, 2022)
A cyber notary is a breakthrough and innovation that is very important in the legal world, especially Notary; through article 15, paragraph 3 of the Notary Position Act, notaries are given the authority to certify transactions electronically. So far, the certification of electronic transactions has been regulated in Law Number 19 of 2016 concerning Information and Electronic Transactions, which discusses all rules relating to electronic transactions. Cyber Notary itself conflicts with the current regulations, especially regarding proof of deeds made electronically by a notary and the authority obtained by a notary as described in Article 15 paragraph 3 of the Law on Notary Positions. This study aims to analyze the powers and responsibilities of a notary about the implementation of a cyber notary in Indonesia. The research method used is normative, using secondary data obtained from library research, including primary, secondary, and tertiary legal sources. The Notary's authority obtained in the cyber Notary is the authority to register online through the AHU Online application, including registration of the deed of establishment of PT, amendments to the articles of association of PT, fiduciary, and will. The deed made by the Notary electronically and in electronic and digital form has the power of proof under the hand.Keywords: Cyber Notary, Electronic Transactions, Power of Evidence.